hay guys what am i doing wrong?

I don’t think I made any mistakes.

-1 = i * i = -1^-2 * -1^-2 = b^-2[/b] = 1^-2 = 1

Yeah you did. i != (-1^-2), i = (-1^(1/2))

oh shit i mixed them up replace all instances with ^-2 with ^[1/2]


= i * i
= [-1^[1/2]] * [-1^[1/2]]
= [-1*-1]^[1/2]
= 1^[1/2]
= 1

-1 = 1

D’oh! TD beat me to it.

Setz, our budding mathematician. :slight_smile:

i ^ x * i ^ x = i ^ 2x

Setz maybe you should learn basic rules of math better before you try to “prove” that 1 = 0 and such nonsense :confused:

Maybe :confused:

it would be true if he said the absolute value of negative one equals one.

That would make the problem pointless since the absolute value of any negative number is it’s positive counterpart.

Your dad did somthing wrong, he didnt wear on of these

well he did… but he wore it like this!

Charl, that is both hilarious and terrifying. You get an A+.

You guys are all going to cry when Setz finally goes against all mathematical rules and finally proves that 1 does in fact equal 0.

(-1^[1/2]) * (-1^[1/2]) != (-1*-1)^(1/2)

just like

2^4 * 2^4 != (2*2)^4

Setz is using the distributive property backwards. Or incorrectly. Or both.


edit this is a result of a googleimagesearch for MATHS

i don’t know why though


Uh, that second statement is true. Both sides of the equation evaluate to 256. Exponentiation does distribute over multiplication, as long as all the quantities involved are real numbers.

In this case there are imaginary quantities involved so certain things that work with real numbers no longer apply.

I feel stupid now. Yay.

Nice going, DemiGoof!